Beyond Circularity: Building Indonesia’s Co-Economy - Cindy Aristiana (APPS Publications, 2026)
Indonesia has made significant progress in promoting the circular economy to address environmental sustainability. However, many circular economy initiatives struggle because they focus primarily on technological solutions while overlooking the coordination required among multiple stakeholders. This commentary argues that Indonesia should move beyond a resource-centric perspective toward a Co-Economy, where value is co-created through ecosystem orchestration. Using the emerging BUMDes–SPPG–farmer ecosystem as an illustrative case, the article applies platform ecosystem concepts, including ecosystem governance, complementary capabilities, network effects, and multi-actor collaboration, to demonstrate how rural institutions can become ecosystem orchestrators rather than traditional producers. The commentary concludes that Indonesia's competitive advantage will depend less on individual organizational performance and more on its ability to coordinate collaborative ecosystems that generate economic, environmental, and social value simultaneously.